Recent developments in aviation law - Koss, Hugh R. (1999)
Presents seminal appellate authorities from the aviation arena from 1998. Presents also non-aviation appellate authorities having application, and in footnotes gives parenthetical treatment to trial court aviation decisions of particular interest.